A simplified extreme method for determining double‐K fracture parameters of concrete using experimental peak load. Issue 2 (15th July 2016) - Qing, L.B.; Nie, Y.T.; Wang, J; Hu, Y
Abstract: A simplified approach to obtain the double‐ K fracture parameters of concrete for three‐point bending beams was proposed based on the extreme method. With the proposed method, the double‐ K parameters can be easily obtained by the experimental peak load. This method requires fewer parameters or tests than the double‐ K method and the peak load method. It also avoids complicated numerical integral compared with the traditional extreme method. The double‐ K parameters obtained by the proposed method are slightly smaller than those by the double‐ K method, and they do not seem to be influenced by the initial crack length to depth ratio.